KEY ASPECTS OF CORPORATE FINANCIAL SOUNDNESS - Y. D. Sotneva (Vestnik MGIMO-Universiteta)
With increasing role of transnational corporation (TNC) questions of corporate financial soundness analysis and prediction methods are gaining momentum. This article highlights the key aspects of financial soundness of corporations. The author compared the economic notion of financial soundness in theory and in practice. Also, specified the concept of financial soundness («stability», «sustainability», «solvency», «soundness», «financial distress) used in Russia and internationally. The existing academic approach in terms of financial soundness assessment is different from the view of international organizations and corporations. The article stated that Russian researches in general see financial soundness as a mix of liquidity and solvency whereas in practice the financial soundness is a more multivariate concept. International Monetary Fund, Ministry of Regional Development and Central Bank of Russia extend the concept of financial soundness adding the profitability and specific ration into the analysis. Foreign authors use different models of financial soundness ranging from statistical, mathematical to special ratings. In practice there is also no definitive understanding of financial soundness based on the analysis of financial information of Rosneft, Alrosa, and Tatneft.Compared Russian and foreign academic approach, government and international instructions of IMF, Ministry of Regional Development and Central Bank of Russia and stated the main characteristics of financial soundness, an author gives its definition.